Crystal structure and Hirshfeld surface analysis of a new polymorph of chloridobis(1,10-phenanthroline-κ2N,N′)copper(II) perchlorate - Maksym O. Plutenko; Oleksandr S. Vynohradov; Matti Haukka; Irina A. Golenya; Snizhana V. Gaidai (Acta Crystallographica Section E: Crystallographic Communications)
The title salt (systematic name: 2-methyl-4-oxo-3,4-dihydroquinazolin-1-ium chloride), [CuCl(C12H8N2)2](ClO4), is comprised of a mononuclear complex cation [Cu(phen)2Cl]+ (phen is 1,10-phenanthroline) and a perchlorate anion, ClO4−, both with point group symmetry 2. The CuII atom has a slightly distorted trigonal–bipyramidal coordination environment, defined by a N4Cl coordination set with the Cl atom and two N atoms at the equatorial sites. In the crystal, each phen ring is parallel to neighboring phen rings. The resulting significant π–π stacking interactions lead to zigzag chains extending parallel to [001]. Hirshfeld surface analysis suggests that the most important contributions to the surface contacts are from H...H (32.1%), H...C/C...H (18.2%), H...O/O...H (14.6%), H...Cl/Cl...H (12.7%) and C...C (10.6%) interactions.